Introducing A.E. Housman (1859-1936) : preliminary studies - Sutton, D. Antoine (Cambridge Scholars Publishing, 2018)
This volume is pivotal reading for laypersons looking for an accurate understanding of the private life and public career of A.E. Housman. Furthermore, it is also essential for any reader seeking to recover a truer image of the Victorian man who, during his lifetime, issued two collections of Romantic poems, A Shropshire Lad and Last Poems. It will be of particular interest to history buffs, poets, professors and students of classical studies, and instructors in literary criticism, given that it sketches Housman's biography and examines in detail his scholarship.